You are on page 1of 17

# Metodo da Particao da Unidade

6 de setembro de 2006

Sumario
1 Introduction 2

2 Some preliminaries 2

3 Getting a procedure 5

## 5 Existence and uniqueness 11

6 Examples 12
6.1 Diagonal C cases . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 13
6.1.1 Case 1: s = 2 and k=1 . . . . . . . . . . . . . . . . . . . . . 13
6.1.2 Case 2: s = 3 and k=1 . . . . . . . . . . . . . . . . . . . . . 13
6.1.3 Case 3: s = 3 and k=2 . . . . . . . . . . . . . . . . . . . . . 14
6.2 Non-diagonal C case . . . . . . . . . . . . . . . . . . . . . . . . . . . 14

A Appendix 15
2 SOME PRELIMINARIES

1 Introduction
Customers of the Generalized Finite Element Method (GFEM), the Partiton of
Unity Method (PUM), the hp-Clouds Method (hp-CM) and the Extended Finite
Element Method (EFEM) have the experience of exactly reproducing polynomials,
under suited conditions, by the usual form:

X  s
X s
X 

P (x) = i (x) ai + bni cn (x xi ) , x , (1)
i n=k+1 =0

s
X
where {i } forms a k-reducible partition of unity for the set {xi } and cn (xxi )
=0
are s k linearly independent polynomials of degree greater than k and less or equal
s.
Nevertheless, there is no guarantee wether such representation, Eq.1, exists or
not, and under which conditons it holds, except for polynomials of degree less or
equal k, which can be easily verified by making bni = 0, n, and taking into account
{i } is k-reducible. A close clue is given by the Reproduction Formula proposed by
Duarte, but it is still a bit far from evidence the existence of such form, Eq.1.
in Eq.1 satisfying the identity above?, or, equivalently, is there a procedure to find
them?, and under which hypothesis do they exist?

2 Some preliminaries
Before demonstration and in order of clearness, it should point out some relevant
propositions and theorems.
First consider a k-reducible partition of unity {i } on for the set {xi } as defined
by Duarte. By definition, such partition of unity exactly reproduces polynomials of
degree less or equal k. This was shown by Duarte in . Consequently any polynomial
P of degree less or equal k verifies:

X
P (x) = i P (xi ), x . (2)
i

## To simplify, without loss of generality, assume cn in Eq.1 such that cn = n

for n = k + 1, k + 2, , s and = k + 1, k + 2, , s, where is the Kronecker
delta. Matricialy it would look like this:

2
2 SOME PRELIMINARIES

c0(k+1) c0(k+2) c0s

c1(k+1) c1(k+2) c1s

.. .. .. ..

. . . .

ck(k+1) ck(k+2) cks
C = (cn )(s+1)(sk) = (3)

1 0 0

0 1 0

.. .. .. ..

. . . .

0 0 1
Plays a fundamental role as the starting point to achieve the desired procedure
the Reproduction Formula proposed by Duarte:

## Theorem 2.1 Let {i } be a k-reducible partition of unity. Let s k + 1. Then the

following formula holds for all polynomials P of degree s 1 :

X  s
X 
()
P (x) = i (x) P (xi ) + P (xi )(x xi ) , x . (4)
i =k+1

Before going on, let make a pause to introduce an ilustrative problem. At first
glance, the coefficients ai and bni in Eq.1 should be straightly determined comparing
Eqs.1 and 4. But soon one is in touch with a not simple task. Inside the square
brackets in Eq.1, after changing the order of the summation and spliting them,
results for comparison with Eq.4:

X  s
X k
X s
X s
X s
X 

i ai + bni c0n + (x xi ) bni cn + (x xi ) bni cn .
i n=k+1 =1 n=k+1 =k+1 n=k+1

As can be seen above, the second summations inside the square brackets remain
with no pair of comparison in Eq.4, deserving a tricky manner to overcome it.
Especial and important results will be shown and demonstrated in the following.
The last one gives a tricky clue to find the procedure.

Proposition 2.1 Let {i } be a k-reducible partition of unity on for the set {xi }.
Let m be an integer such that 0 m k. Then:

X
(x xi )km i = 0, x . (5)
i

1
The superscript () in Eq.4 stands for derivative of order , and the coefficients are given
recursively in Duarte.

3
2 SOME PRELIMINARIES

Proof: Developing the left term in the above equation, taking into account the
binomial theorem:

X km  
km k m
X X
(x xi ) km
i = (1) x xkm
i i
i i =0

km   X
km k m
X
= (1) x xkm
i i . (6)
=0
i

X
xkm
i i = xkm , x .
i

## Coming back to Eq.6:

km 
X
km
X k m km
km
(x xi ) i = (1) x
i =0

km  
km k m
X
km
= x (1) = 0. (7)
=0

## The binomial theorem is implicit in the above result. The demonstration is

complete. 

Proposition 2.2 Assume the same hypothesis of Proposition 2.1. Let n be any
positive integer and mn be a real. Then:

n  
X
n km
XX n n
mn x (x xi ) i = mn xi (x xi )km+ i = 0, x .
i i =0

(8)

## Proof: By Proposition 2.1 one immediately have:

X
mn xn (x xi )km i = 0.
i

## Again, by the binomial theorem:

4
3 GETTING A PROCEDURE

X
mn xn (x xi )km i =
i
X
= mn (x xi + xi )n (x xi )km i
i
n  
X X n
= mn (x xi ) xn
i (x xi )km i
i
=0
n  
XX n n
= mn xi (x xi )km+ i .
i =0

## The demonstration is complete. 

3 Getting a procedure
With the help of Proposition 2.2, the Reproduction Formula can be rewritten for
xs as:

X  s
X s
s
x = i xsi + ! xs
i (x xi ) +
i =k+1

k1 X
sk X
n   
X n n km+
+ mn xi (x xi ) .
m=0 n=0 =0

In the above equation the last term in square brackets is null. This is remarkable
because is the starting trick to achieve the procedure. In order to group both
summations in the square brackets, calling the power of x xi , the power of
xi and adjusting accordingly the extremes in the right sum, after a lot of algebra
which can be found in Appendix A, one get 2 :
2
In what follows, the upper bound lower than the inferior means no summation.

5
3 GETTING A PROCEDURE

X 
s
x = i xsi +
i
s  
X s
+ ! xs
i (x xi ) +
k+1

sk min(k1,s)
k X  
X X ++mk
+ m(++mk) xi (x xi )
=1 =0 m=k
+mk
s s min(k1,s)   
X X X ++mk
+ m(++mk) xi (x xi )
=k+1 =0 m=0
+mk

## For brevity, calling:

 
++mk
Am = m(++mk) ,
+mk

r() = min(k 1, s )

and grouping the third and fourth terms in the square brackets in the summation
over , Eq.9 yields:

X 
s
x = i xsi +
i
k sk r()
X X X

+ (x xi ) xi Am
=1 =0 m=k
s    s r() 
X s s
X

X
+ (x xi ) ! xi + xi Am
=k+1
=0 m=0

Using the Kronecker delta, the term on xsi inside the square brackets can be
replaced by a summation of xi terms, resulting:

6
3 GETTING A PROCEDURE

X 
s
x = i xsi +
i
k sk r()
X X X

+ (x xi ) xi Am
=1 =0 m=k
s s    r() 
X

X s X
+ (x xi ) xi ! (s) + Am
=k+1 =0
m=0

## On the other hand, Eq.1 suggests another manner to represent xs , i. e.:

X  s
X n
X 
s
x = i ai + bni cn (x xi ) . (9)
i n=k+1 =0

For the purpose of comparison between both, Eq.9 and Eq.9, dismembering the
right term above gives:

X  s
X
s
x = i ai + bni c0n (10)
i n=k+1
k
X s
X

+ (x xi ) bni cn + (11)
=1 n=k+1
Xs Xs 

+ (x xi ) bni cn . (12)
=k+1 n=k+1

After subtracting Eq.9 from Eq.10, and remarking that the identity is verified
for any (x xi ) , results three new equations:
s
X
ai = xsi bni c0n , (13)
n=k+1

s sk r()
X X X
bni cn = xi Am , 1 k, (14)
n=k+1 =0 m=k

s s    r() 
X X s X
bni cn = xi ! (s) + Am , k + 1 s. (15)
n=k+1 =0
m=0

## Now regarding the hypothesis on cn , an expression for bi is immediately achieved

from Eq.15:

7
3 GETTING A PROCEDURE

s    r() 
X s X
bi = xi ! (s) + Am , k + 1 s. (16)
=0
m=0

## Substitution of Eq.16 in Eq.14 furnishes:

s sn    r(n) 
X X s X
cn xi n! (sn) n + Anm =
n=k+1 =0
n m=0
sk r()
X X
= xi Am , k + 1 n s and 1 k, (17)
=0 m=k

On the left side of the above equation, changing the order of the summations
and extending the summation over till s k with the help of the Kronecker delta,
gives:

sk s    r(n) 
X X s X
xi (1 (sk) )cn n! (sn) n + Anm =
=0 n=k+1
n m=0
sk r()
X X
= xi Am , k + 1 n s and 1 k, (18)
=0 m=k

## Imposing equality for any xi in the above equation, results:

s    r(n) 
X s X
(1 (sk) )cn n! (sn) n + Anm =
n=k+1
n m=0
r()
X
= Am , 0 s k 1. (19)
m=k

Or rearranging in such a manner that the A coefficients are left on the same side:

r() s r(n)
X X X
Am (1 (sk) )cn Anm =
m=k n=k+1 m=0
s
 
X s
= n! (1 (sk) )(sn) n cn , 0 s k 1. (20)
n=k+1
n

8
3 GETTING A PROCEDURE

## Aiming at finding the imposed coefficients, substituting A given by Eq. fur-

nishes:

r()  
X ++mk
m(++mk)
m=k
+mk
s r(n)  
X X n++mk
(1 (sk) )cn m(n++mk) =
n=k+1 m=0
n+mk
s  
X s
= n! (1 (sk) )(sn) n cn , 0 s k 1. (21)
n=k+1
n

## The first summation in the above equation can be rewritten as:

r()  
X ++mk
m(++mk) =
m=k
+mk
  r()  
X ++mk
= (k) + m(++mk) ,
0 m=k+1
+mk
+ 1 + + m k s k 1. (22)

## Regarding these, Eq.21 can be rewritten as:

s r(n)  
X X n++mk
(k) =(1 (sk) ) cn m(n++mk)
n=k+1 m=0
n+mk
r()  
X ++mk
m(++mk) +
m=k+1
+mk
s  
X s
+(1 (sk) ) n! (sn) n cn ,
n=k+1
n
+ 1 n + + m k s k 1 and
+ 1 + + m k s k 1. (23)

## In Eq.23 both, n + + m k and + + m k, are greater than . Also

9
4 LESS DEGREE POLYNOMIAL REPRODUCTION

notes that = s k makes the upper bound in the first and second summations less
than the inferior one, i.e., no sum involving coefficients takes place. This means
that coefficients of the form (k)(sk) can be obtained independently of any
coefficients. These two remarks above allow the following algorithm for determining
the coefficients:
begin
for from s k down to 0 do
for from 1 to k do
determine (k) by Eq.23
end

## 4 Less degree polynomial reproduction

The procedure already developed is restricted to polynomials of degree s. No
effort has been devoted yet to less degree polynomials, i.e., degree between k and s.
The question is wether exist ai and bni such that:

X  s
X s
X 
p
x = i (x) ai + bni cn (x xi ) , k < p < s. (24)
i n=k+1 =0

To begin with, consider p, k < p < s. It was proved that there are ai and bni
such that:
 p p 
X X X
p
x (x) = i (x) ai + bni cn (x xi ) , x , (25)
i n=k+1 =0

p
X
noting cn (x xi ) are of order less or equal p, and holding the same hypothesis
=0
on cn , 0 s, Eq.3. With no loss of generality, in Eq.24, remarking cn = n ,
k + 1 n, s, and taking ai = ai , bni = bni , k + 1 n p, and bni = 0,
p + 1 n s, results:

10
5 EXISTENCE AND UNIQUENESS

X  s
X s
X 

i (x) ai + bni cn (x xi ) =
i n=k+1 =0
 p s s s 
X X X X X

= i (x) ai + bni cn (x xi ) + bni cn (x xi )
i n=k+1 =0 n=p+1 =0
 p s 
X X X

= i (x) ai + bni cn (x xi )
i n=k+1 =0
 p p p s 
X X X X X

= i (x) ai + bni cn (x xi ) + bni n (x xi )
i n=k+1 =0 n=k+1 =p+1
 p p 
X X X

= i (x) ai + bni cn (x xi ) = xp .

i n=k+1 =0

## 5 Existence and uniqueness

Once the coefficients are found, coming back to Eq.16, bi , k + 1 s,
can finally be obtained. Consequently, ai can be calculated with the aid of the
bi already computed. Moreover, as the above algorithm obviously shows, the
coefficients exist for all s and {xi } chosen for the partition of unit, providing the
hypothesis on cn be held. So do bi and ai .
The hypothesis on cn may even be relaxed, say sub-matrix (cn )sk(sk) must be
invertible, which is guaranteed by the hypothesis on the linear independence of the
Xs
polynomials cn (x xi ) . To see this, let cn , 0 s and k + 1 n s, be
=0
s
X
coefficients such that there exist c1
n verifying cm c1
mn = n , k + 1 , n s.
m=k+1
Taking:
s
X
cn = cm c1
mn , 0 s, (26)
m=k+1

it has already been shown that there exists bni such that:

X  s
X s
X 
p
x (x) = i (x) ai + bni cn (x xi ) , k + 1 p s. (27)
i n=k+1 =0

s
X
Assuming ai = ai , bni = cnl bli and considering Eq.26, after substituting in
l=k+1

11
6 EXAMPLES

Eq.27, results:

X  s
X s
X s
X s
X 
p 1
x = i ai + cnl bli cm cmn (x xi )
i n=k+1 l=k+1 =0 m=k+1
X  s
X s
X s
X s
X 
= i ai + bli cnl cm c1
mn (x

xi )
i =0 l=k+1 n=k+1 m=k+1
X  Xs Xs Xs 

= i ai + bli ml cm (x xi )
i =0 l=k+1 m=k+1
X  Xs Xs 

= i ai + bmi cm (x xi )
i =0 m=k+1
X  Xs Xs 

= i ai + bmi cm (x xi ) ,
i m=k+1 =0

s
X
So, there exist ai = ai and bni = c1
nm bmi such that:
m=k+1
X  s
X s
X s
X 
xp = i ai + bni
cn (x xi ) . (28)
i =0 n=k+1 =0

## Therefore, the existence of the coefficients ai and bi is guaranteed whenever ma-

s
X
trix (cn )(sk)(sk) is invertible, or equivalently, whenever the polynomials cn (x
=0
xi ) , k + 1 n s, are able to generate polynomials of the form:

## where k + 1 p s and r is a polynomial of degree less or equal k.

The uniqueness of such coefficients is beyond the scope of this article, and is
left for future work. But the point is wether fi 0 is the unique solution of
X
i (x)fi (x) = 0, x , or not.
i

6 Examples
To ilustrate the theorem just presented, consider two series of examples. The
first refers to the especial case which the coefficientes c are of the type of Eq.3, and
the second

12
6.1 Diagonal C cases 6 EXAMPLES

## 6.1 Diagonal C cases

6.1.1 Case 1: s = 2 and k = 1

c02
C = c12

1
ai = c02 + x2i
bi = { b0i 1 }T

X
i (2x2 x + c12 xi c12 x) =
i
X X
= i (2x2 x) = i x2 = x2
i i

## 6.1.2 Case 2: s = 3 and k = 1

c02 c03

c12 c13
C =

1 0

0 1
ai = 3c02 (c12 + xi ) + 2c03 + x3i
bi = { b0i 3(c12 + xi ) 2 }T

X
i (3xi x2 2x3 + 3c212 xi 3c212 x + 3c12 xi x 3c12 x2 + 2c13 xi 2c13 x) =
i
X X
= i (3x3 2x3 ) = i x3 = x3
i i

13
6.2 Non-diagonal C case 6 EXAMPLES

## 6.1.3 Case 3: s = 3 and k = 2

c03

c13
C =

c23

1
ai = c03 + x3i
bi = { b0i b1i 1 }T

X
i (x3 + 3x2i x 3xi x2 + c23 x2 + c23 x2i 2c23 xi x + c13 x c13 xi ) =
i
X X
= i (x3 + 3x3 3x3 ) = i x3 = x3
i i

## 6.2 Non-diagonal C case

1 1 1
1 1 1

C=
1 2 1

1 1 2

2 1 1
1 1 1

4 4 4
1 1 1
4 4 4

1 0 0

0 1 0

0 0 1

29 11 3
ai = + xi + x2i + x4i
16 4 2

b1i

19 + 11 x + 3 x2

16 4 i 2 i
bi = 15 1 9 2

16
x
4 i
x
2 i

5 21 x + 3 x2

16 4 i 2 i

14
A APPENDIX

 
X 29 29 11 11 2 3 2 3 3
i 4xi x 3x + xi x + xi x x + xi x x = x4
3 4

i
16 16 4 4 2 2

A Appendix
First remark the restrictions on m, n and :

0mk1 (29)
0nsk1 (30)
0 n. (31)

By definition, let:

=km+ (32)
= n . (33)

## Adding both equation above results:

+ = n m + k. (34)

## Assume as an independent summation index. Then, by Eqs.29-30 and Eq.33,

one immediatelly finds:

1 s 1.

## Now is constrained by Eqs.30-31 and Eq.32 to 0 s k 1, and by

Eqs.29-30 and Eq.34 to 0 s 1. Joining both, results the restriction on
:

## Remark on Eq.35 that min(s 1, s k 1) = s k 1, if 1 k, and

min(s 1, s k 1) = s 1, if > k. This fact suggests dismembering
the summation on in two others summations.
Moreover:

15
A APPENDIX

0mk1
0n=++mk sk1k ms1
0 m + k n k m n + k = m + ,

or equivalently:

## If 1 k, then k m min(k 1, s 1), and, if > k, then

0 m min(k 1, s 1).
Taking into account the results above one can rewrite:

k1 sk1
X X X n X X min(k1,s1)
k sk1 X X X min(k1,s1)
s1 s1 X
= + .
m=0 n=0 =0 =1 =0 m=k =k+1 =0 m=0

16
Referencias REFERENCIAS

Referencias

17